Psychological Well-Being of Maritime Communities: An Analysis Based on Social Support, Self-Esteem, and Resilience - Yuliasari, Hesty; Nirmalasari, Novita; Fatimah , Malida; Herawati, Icha (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2026)
This study aims to examine the relationship between social support, self-esteem, and resilience on psychological well-being in maritime communities. This study used a correlational design involving 87 respondents with the criteria of maritime communities, living in coastal areas, male or female, and aged 18-65 years old, measured through a modified scale of the Social Support scale, Rosenberg's Self Esteem Scale (RSES), resilience scale, and Ryff's Psychological Well-Being Scale (RPWBS). The results of the analysis showed that social support, self-esteem, and resilience together were predictors of psychological well-being in maritime communities. Partially, social support significantly influenced psychological well-being. This result demonstrates that maritime communities are part of a community that promotes well-being in the psychological, family, and social spheres. Social support, self-esteem, and resilience influence a person's psychological well-being, with social support, resilience, and self-esteem being important indicators of positive mental health. These support helps individuals cope with adverse situations and stressors, while self-esteem fosters self-acceptance, self-responsibility, and self-care.